Pemberdayaan Masyarakat Melalui Pengolahan Tempurung Kelapa Menjadi Produk Kerajinan - Sabaruddin, Abdul Sabaruddin (Cattleya Darmaya Fortuna, 2025)
Ranojaya Village, Toari Sub-district, has the potential for coconut plantations. However, coconut shell waste is not optimally utilized, due to lacking community knowledge. This community service aims to empower the community through processing coconut shells into economically valuable handicraft products. This activity includes several stages, namely observation, planning, implementation, and evaluation. In the implementation stage, the community was trained to process coconut shells into craft products, such as key chains, decorative lamps, ashtrays, and wall hangings. The results of this program showed an increase in community skills in processing coconut shells and a growing awareness of their economic potential.